Daya Pragmatik Tindak Tutur Ekspresif dalam Film Budi Pekerti Karya Wregas Bhanuteja - Siti Fara Dibah; Wini Tarmini (EduInovasi: Journal of Basic Educational Studies, 2024)
The purpose of this study is motivated by the researcher's desire to know the expressive illocutionary speech acts in the movie Budi Pekerti. This paper aims to identify the types of expressive illocutionary speech acts spoken by the characters in the movie "Budi Pekerti". This research uses data collection method in the form of listening method followed by free listening technique and note taking technique. Furthermore, the data were analyzed using pragmatic studies. The data source is obtained from the dialog fragments of the film "Budi Pekerti". The results of the research on the film "Budi Pekerti" show the use of seven types of expressive illocutionary speech acts, namely expressive speech acts of thanking, praising, congratulating, criticizing, complaining, blaming, and flattering expressive speech acts.